2012
DOI: 10.1111/j.1600-0897.2012.01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Changes in the Level of the Innate Immune Molecule, Surfactant Protein‐A, and Cytokines in Vaginal Fluid

Abstract: PROBLEM Our knowledge of the innate host-defenses in the vagina, a site where these defenses are essential to protecting the host upper reproductive tract from invasion by pathogens, is as yet rudimentary. Specifically, little is known about the pattern-recognition component of vaginal innate immunity, the relationship of pattern-recognition molecules to known cytokine levels, and the role of gonadal hormones in their regulation. METHOD OF STUDY We measured levels of Surfactant Protein-A (SP-A), a prototypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Several other studies have described altered levels of immune mediators through stages of the cycle [51,52,56,57]. One explanation for variable findings across studies might be that cycle length in women are different, and samples might not have been collected at exactly the same time of the cycle in different studies.…”
Section: A N U S C R I P Tmentioning
confidence: 90%
“…Several other studies have described altered levels of immune mediators through stages of the cycle [51,52,56,57]. One explanation for variable findings across studies might be that cycle length in women are different, and samples might not have been collected at exactly the same time of the cycle in different studies.…”
Section: A N U S C R I P Tmentioning
confidence: 90%
“…The absence of consistent mid-cycle decreases in HBD2, elafin and the other cytokines suggests that VEC, despite their ability to produce antimicrobials, are not exclusive or major contributors to the mid-cycle decline observed elsewhere 23 . Unfortunately, previous publications provide a complicated backdrop against which to make comparisons, and it is still unclear whether a mid-cycle drop in cytokine, chemokine or antimicrobial levels occurs in vivo 23, 32, 33 . For example, Keller et al (2007) demonstrated that antimicrobials, cytokines and chemokines including SLPI, HBD2, IL-8 and lactoferrin decrease at mid-cycle in CVL recovered from healthy premenopausal women while total protein concentration remains relatively constant 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Contained within the fluid are various immunomodulatory molecules including cytokines, chemokines, antimicrobial proteins, enzymes and growth factors. In cervico-vaginal lavage fluid (CVL fluid), the concentrations of antimicrobial proteins such as SLPI, HBD2, human neutrophil peptide 1 (HNP1; also known as neutrophil defensin 1), HNP2, HNP3, lysozyme, lactoferrin and surfactant A markedly decrease by mid-cycle (day 13) and remain low for 7–10 days during the secretory phase before returning to the higher levels found during the proliferative phase following menstruation 26,27 . These findings suggest that the antimicrobial contribution of the luminal fluid to overall immune protection in the FRT decreases during the secretory phase.…”
Section: Immune Protection Of the Frtmentioning
confidence: 99%